Radiation oncology : difficult cases and practical management - Small, William, Jr; Williams, Tim R.; Donnelly, Eric D. (Demos Medical, 2013)
Radiation Oncology provides residents, fellows, and clinicians with a practical, evidence-based guide to the current management of difficult cases in radiation oncology. Emphasis is on the management of those clinical challenges commonly seen in practice that the community practitioner would normally handle without outside referral. The book offers comparisons of treatment approaches to difficult situations, allowing the reader to compare their current treatment approach to that of experts and others in the community. Radiation Oncology is organized in seven sections corresponding to the major.